2010
DOI: 10.1136/pgmj.2010.104976
|View full text |Cite
|
Sign up to set email alerts
|

Emergency presentations of Parkinson's disease: early recognition and treatment are crucial for optimum outcome

Abstract: Parkinson's disease (PD) is a debilitating condition associated with significant morbidity and mortality. Pathophysiologically the illness is due to a disruption of dopamine production in the basal ganglia and leads to a wide array of symptoms. These symptoms are not restricted to the nervous system; thus, the illness often presents acutely to a wide range of specialties, many of which may have limited experience in the condition. Patients often become unwell with illnesses unrelated to their PD. However, thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 83 publications
0
21
0
Order By: Relevance
“…Although the incidence rate has decreased year by year due to doctors’ improved knowledge of NMLS, studies have shown that mortality in NMLS is between 10% and 30% 2. Sudden withdrawal and abrupt reduction of antiparkinsonian drugs are major risk factors, especially dopamine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the incidence rate has decreased year by year due to doctors’ improved knowledge of NMLS, studies have shown that mortality in NMLS is between 10% and 30% 2. Sudden withdrawal and abrupt reduction of antiparkinsonian drugs are major risk factors, especially dopamine.…”
Section: Discussionmentioning
confidence: 99%
“…This disease is named after neuroleptic malignant syndrome (NMS), a dangerous adverse response to antipsychotic drugs, due to similar clinical manifestations. The syndrome is characterized by such symptoms as hyperthermia, muscle rigidity or tremor, altered consciousness, autonomic instability, and elevated serum creatine-kinase (CK) levels 2. The incidence rate has decreased year by year due to doctors’ improved knowledge of NMLS.…”
Section: Introductionmentioning
confidence: 99%
“…In more severe cases, neuropsychiatric manifestations, altered conscious level and cardiovascular collapse is seen. Dysphagia and hypersalivation are useful signs that can help differentiate NMLS from the main differential diagnosis, serotonin syndrome, 19 which may also be seen in patients treated with selective serotonin reuptake inhibitors (SSRIs), in particular fluoxetine or fluvoxamine (and mainly when these are co-administered with selegiline). Immediate management is essential as there is a significant risk of mortality.…”
Section: Dopamine Agonist Withdrawalmentioning
confidence: 99%
“…A global estimate of the number of people with Parkinson's disease (PD) over the age of 50 years is between 4.1 and 4.6 million [2]. In those 80 years and older PD has a prevalence of 2% [3]. By 2030, this number is expected to double to between 8.7 and 9.3 million people.…”
Section: Introductionmentioning
confidence: 99%
“…PD is the second most common neurodegenerative disorder after Alzheimer's disease. The risk of developing PD increases with age 3 and is characterised by a progressive degeneration of pigmented neurons in the substantia nigra in the mid brain [6]. This causes a deficiency in dopamine, which is responsible for controlled and smooth muscle movement.…”
Section: Introductionmentioning
confidence: 99%